Resenha do Livro: WYNARCZYk, HILáRIO. CiuDADANOs DE DOs MuNDOs: EL MOViMiENTO EVANGÉLiCO ViDA PúBLiCA ARGENTiNA 1980-2001. BUENOS AIRES: UNSAM EDITA, 2009. 329 P - Meirelles, Mauro (Debates do NER, 2010)
Resenha do Livro: WYNARCZYk, HILáRIO. CiuDADANOs DE DOs MuNDOs: EL MOViMiENTO EVANGÉLiCO ViDA PúBLiCA ARGENTiNA 1980-2001. BUENOS AIRES: UNSAM EDITA, 2009. 329 P